2016
DOI: 10.1038/srep32811
|View full text |Cite
|
Sign up to set email alerts
|

Xanthomonas campestris FabH is required for branched-chain fatty acid and DSF-family quorum sensing signal biosynthesis

Abstract: Xanthomonas campestris pv. campestris (Xcc), a Gram-negative phytopathogenic bacterium, causes black rot disease of cruciferous vegetables. Although Xcc has a complex fatty acid profile comprised of straight-chain fatty acids and branched-chain fatty acids (BCFAs), and encodes a complete set of genes required for fatty acid synthesis, there is still little known about the mechanism of BCFA synthesis. We reported that expression of Xcc fabH restores the growth of Ralstonia solanacearum fabH mutant, and this all… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
20
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 18 publications
(22 citation statements)
references
References 52 publications
2
20
0
Order By: Relevance
“…Although supplementing with valine and isoleucine mixtures increased the percentage of BCFAs, especially anteiso -C 15:0 , and decreased the amount of UFAs in Xcc membrane lipids, Xcc significantly increased UFAs at low temperature, even when supplemented with high concentrations of valine and isoleucine mixtures at low temperature, which indicated that BCFAs did not have a major effect on response to a decrease in ambient temperature. These results were consistent with previous studies that replacement of Xcc fabH with E. coli fabH caused Xcc to lose the ability to synthesize BCFAs, but the mutant strain grew well at low temperature ( Yu et al, 2016 ). This confirms that the adaptive mechanism to low temperature in Xcc differs from that in L. monocytogenes , which mainly stimulates anteiso -BCFA biosynthesis to increase membrane disorder in response to low temperatures ( Zhu et al, 2005a , b ).…”
Section: Discussionsupporting
confidence: 93%
See 3 more Smart Citations
“…Although supplementing with valine and isoleucine mixtures increased the percentage of BCFAs, especially anteiso -C 15:0 , and decreased the amount of UFAs in Xcc membrane lipids, Xcc significantly increased UFAs at low temperature, even when supplemented with high concentrations of valine and isoleucine mixtures at low temperature, which indicated that BCFAs did not have a major effect on response to a decrease in ambient temperature. These results were consistent with previous studies that replacement of Xcc fabH with E. coli fabH caused Xcc to lose the ability to synthesize BCFAs, but the mutant strain grew well at low temperature ( Yu et al, 2016 ). This confirms that the adaptive mechanism to low temperature in Xcc differs from that in L. monocytogenes , which mainly stimulates anteiso -BCFA biosynthesis to increase membrane disorder in response to low temperatures ( Zhu et al, 2005a , b ).…”
Section: Discussionsupporting
confidence: 93%
“…The precursors of the DSF-family signal come from the fatty acid synthesis pathway ( Zhou et al, 2015b ; Yu et al, 2016 ). However, though ilvC deletion mutant produced fatty acid normally, the total amount of DSF-family signal production was reduced during its growth.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In this second scenario, X. campestris pv. campestris FabH condensed octanoyl coenzyme A (octanoyl-CoA) with malonyl-ACP to produce 3-oxodecanoyl-ACP ( 24 ), which FabG2 reduced to 3-hydroxydecanoyl-ACP, as described above. Fatty acid synthesis was thus primed, and growth at 42°C proceeded.…”
Section: Resultsmentioning
confidence: 98%